Penerapan Pembelajaran Kooperatif Mata Pelajaran Sejarah Kebudayaan Islam Di MTS Simpang: Implementation of Cooperative Learning in Islamic Culture History Subjects at MTS Simpang - Julia, Rispa (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to describe the application of cooperative learning models in the subject of Islamic Cultural History (SKI) at MTs Simpang, West Pasaman Regency. This research used a descriptive qualitative approach. Data were collected through observation, interview, and documentation. The results showed that teachers applied several cooperative learning models such as Jigsaw, Student Teams Achievement Division (STAD), and Team Game Tournament (TGT). These models are chosen to increase students' activeness, encourage cooperation, and instill Islamic character values through group interaction. Cooperative learning is proven to be able to create a pleasant learning atmosphere, increase students' learning motivation, and help students understand the material more deeply. Obstacles in implementation such as differences in participation levels between students can be overcome through the division of heterogeneous groups and appropriate classroom management strategies. Thus, the application of cooperative learning is an effective strategy in improving the quality of SKI learning at MTs Simpang.